1992
DOI: 10.1111/j.1471-4159.1992.tb09751.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphotyrosine in Mouse Brain: Developmental Changes and Regulation by Epidermal Growth Factor, Type I Insulin‐Like Growth Factor, and Insulin

Abstract: Using antiphosphotyrosine antibodies, we have investigated protein phosphorylation in mouse brain during development in intact animals and in reaggregated cerebral cultures. Under basal conditions, in vivo and in vitro, the levels of two main phosphoproteins, of Mr 120,000 and 180,000 (pp180), increased with development, reaching a maximum in the early postnatal period and decreasing thereafter. In adult forebrain, pp180 was still highly phosphorylated, but it was not detected in cerebellum or in peripheral ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
4
14
0
Order By: Relevance
“…Of special interest in the present context is a protein of 180 kDa reported by several groups to be a major phosphoprotein of neuronal tissue in vivo (32,38) and in vitro (34). A protein termed ppl80 is present in neurons but not glia and is abundant in the adult cortex, hippocampus, and striatum but not in the adult cerebellum, spinal cord, pituitary gland, and other tissues (34). A glycoprotein termed PSD-GP180 is a constituent of the postsynaptic density and is also a substrate for Ca2+/ calmodulin protein kinase (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of special interest in the present context is a protein of 180 kDa reported by several groups to be a major phosphoprotein of neuronal tissue in vivo (32,38) and in vitro (34). A protein termed ppl80 is present in neurons but not glia and is abundant in the adult cortex, hippocampus, and striatum but not in the adult cerebellum, spinal cord, pituitary gland, and other tissues (34). A glycoprotein termed PSD-GP180 is a constituent of the postsynaptic density and is also a substrate for Ca2+/ calmodulin protein kinase (38).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of protein tyrosine kinase in the adult nervous system is high compared to that in other tissues, and tyrosine-phosphorylated proteins are mainly localized in neurons and synapses (10,(29)(30)(31)(32)(33). The tyrosine phosphorylation of some of these proteins has been reported to be controlled by growth factors, depolarization, dopaminergic innervation, glutamatergic agonists, Ca2+ ionophores, and phorbol esters (34)(35)(36)(37). Of special interest in the present context is a protein of 180 kDa reported by several groups to be a major phosphoprotein of neuronal tissue in vivo (32,38) and in vitro (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their corresponding receptors are similar in their subunit structure and molecular size, and they display cross-reactivity in response to high concentrations of ligand (32)(33)(34). Both EGF receptors and IGF-1 receptors belong to the family of tyrosine protein kinases, and they have been shown to phosphorylate some proteins in common (35). It also has been shown that both EGF and IGF-1 can regulate proliferation of the same cells (36).…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, the tyrosine phosphorylation machinery appears to be concentrated at the level of synapses on the pre-and postsynaptic sides (for review, see ref. 13) and is particularly active at the time of synaptogenesis during development (14)(15)(16). At the neuromuscularjunction, recent evidence indicates that postsynaptic tyrosine phosphorylation is regulated by neuron-target interactions (17,18) and by growth factors (19).…”
mentioning
confidence: 99%